Austerity bites : a journey to the sharp end of cuts in the UK - O'Hara, Mary (Policy Press, 2014)
Voted one of the Guardian best books of 2014 by Owen Jones. After coming to power in May 2010, the Coalition government in the United Kingdom embarked on a drastic programme of cuts to public spending and introduced a raft of austerity measures that had profoundly damaging effects on much of the population. This bestselling book by award-winning journalist Mary O'Hara chronicles the true impact of austerity on people at the sharp end, based on her 'real-time' 12-month journey around the country just as the most radical reforms were being rolled out in 2012 and 2013. Drawing on hundreds of hours of compelling first-person interviews, with a broad spectrum of people ranging from homeless teenagers, older job-seekers, pensioners, charity workers, employment advisers and youth workers, as well as an extensive body of research and reports, the book explores the grim reality of living under the biggest shakeup of the welfare state in 60 years. with a new Foreword by Mark Blyth, Professor of International Political economy and International Studies at Brown University, USA, Austerity Bites dispels any notion that "we are all in this together" and offers an alternative to the dominant and simplistic narrative that we inhabit a country of "skivers versus strivers.